The Effect of Comic Strips as an English Teaching Media toward Students’ Reading Ability in Descriptive Text - Arino Susanto; Absharini Kardena (EDUTEC : Journal of Education And Technology, 2021)
This research was done due to the lack of students' reading ability in descriptive text in MTsS Yati Kamang. This research was classified as a quasi-experimental research. To experiment class the researcher choose VII.II class and VII.I is experiment class. The researcher uses test to measure students’ reading ability. Afterwards, the researcher proved that the Comic strip as a media was able to increase students' reading ability in descriptive text. Experiment class and control class there are 38 students. There were 19 students as the respondents in experimental group and 19 students as the respondents in control group. The experimental class was taught by using Comic strips as media in teaching and the control group was taught only by using Picture. The result of paired sample t-test showed that the tobtained (6,591) was higher than ttable(2,326) with the level significant 0,01. The null hypothesis was rejected and the alternative hypothesis was accepted. It means there is a significant effect of using Comic strips toward students’ reading ability in descriptive text at the seventh grade of MTsS Yati Kamang.